Breast cancer prognostic classifiers: combining clinical with molecular profiles - Muftah, Abir A. Abdelhadi (2017)
Background and aims While current prognostic tools for breast cancer (BC) provide valuable information on behaviour and outcome, there are growing concerns that these parameters are not sufficient to reflect the degree of heterogeneity or to guide management decisions at individual patient level. Therefore, further refinement of the existing prognostic tools is needed. The advent of multi-parameter gene signatures has increased our hope of refining BC prognostic classification; however, their cost and restricted application to certain subgroups of BC limit their clinical usefulness. Molecular taxonomy of BC using intrinsic gene sets has not only improved our understanding of BC biology, but has also provided important prognostic information. Yet, integration of this molecular classification with the clinical parameters remains a challenging task.